Prevalence and risk factors for anxiety in patients with early- and middle-stage lung cancer: a cross-sectional study - Zhang, Ruoqi; Zhang, Peitong; Lin, Yuejie; Guo, Xiuwei; Wang, Jing (Frontiers in Psychology, 2024)
Objective Lung cancer is a leading cause of cancer-related morbidity and mortality worldwide, with patients frequently experiencing significant psychological distress, particularly anxiety. Despite the high prevalence of anxiety in patients with cancer, there is limited comprehensive research focusing on the specific factors influencing anxiety in patients with early- and middle-stage lung cancer within the context of Chinese medicine hospitals. Therefore, we aimed to investigate the epidemiology and factors influencing anxiety disorders in patients with early- and middle-stage primary bronchial lung cancer through a cross-sectional study. Methods A total of 340 patients with early and middle-stage lung cancer admitted to the outpatient ward of the oncology department at Guang’anmen Hospital from June 2023 to December 2023 were included in this study. Survey data, including the patients’ general condition questionnaire, Generalized Anxiety Scale (GAD-7), Hospital Anxiety and Depression Scale (HADS), and Mental Toughness Scale (CD-RISC-10), were collected and recorded in a database using a two-person input format. Data analysis was performed using SPSS 27.0 software. Results Out of the 340 patients with early- and middle-stage lung cancer included in this study, 133 had anxiety, resulting in an overall anxiety detection rate of 39.12%. The chi-square test showed that statistically significant differences in religion, marital status, surgical treatment, tobacco use, and alcohol history between the anxious and non-anxious groups (p < 0.05). Moreover, statistically significant differences were observed in per capita annual family income, pathological type, VAS score, targeted therapy, treatment stage, and mental toughness level (p < 0.001). Other factors were not significantly correlated with anxiety onset. Multivariate logistic regression analysis showed that higher per capita family income and completed treatment independently acted as protective factors against anxiety onset in patients with early- and middle-stage lung cancer. Conversely, rare pathological types, increased pain severity, and lower levels of mental toughness were identified as independent risk factors for anxiety onset in these patients. Conclusion Anxiety was prevalent in patients with early- and middle-stage lung cancers. Rare pathological types, increased pain severity, and lower levels of mental toughness were independent risk factors for anxiety. Therefore, clinicians and psychologists should pay more attention to patients with rare types of tumors, actively manage their pain symptoms, and consider implementing mental resilience training to improve patients’ mental toughness.